Resistance to Reform: Status Quo Bias in the Presence of Individual- Specific Uncertainty - Fernandez, Raquel; Rodrik, Dani (American Economic Review, 1991)
Why do governments so often fail to adopt policies which economists consider to be efficiency-enhancing? Our answer to this question relies on uncertainty regarding the distribution of gains and losses from reform. We show that there is a bias towards the status quo (and hence against efficiency-enhancing reforms) whenever some of the individual gainers and losers from reform cannot be identified beforehand. There are reforms which, once adopted, will receive adequate political support but would have failed to carry the day ex ante. The argument does not rely on risk aversion, irrationality, or hysteresis due to sunk costs.